PENGEMBANGAN LEMBAR KEGIATAN SISWA DENGAN PENDEKATAN SAINTIFIK PADA MATERI TURUNAN SMA - Erlinda Rahma Dewi; Lihar Raudina Izzati; Dita Purwinda Anggrella (Program Studi Pendidikan Matematika, Universitas Muhammadiyah Kupang, 2020)
This study aims to produce student activity sheets with a scientific approach to high school derivative materials and to determine the quality of student activity sheets from the aspects of validity, practicality, and effectiveness. This type of research is development research. The development model used is the ADDIE development model which consists of analysis, design, development, implementation, and evaluation. The instrument used in this study was the Student Activity Sheet assessment sheet to measure the validity, the response questionnaire to the use of learning devices to measure practicality, and the learning outcome test questions to measure effectiveness. The results showed that the Student Activity Sheet developed was valid because the results of the assessment met the minimum classification